Divieto di discriminazione religiosa sul lavoro e organizzazioni religiose (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. La direttiva europea 2000/78/CE e le organizzazioni di tendenza - 2. Il caso Egenberger c. Evangelisches Werk dinanzi alla Corte di giustizia - 3. La sindacabilità dei provvedimenti confessionali in materia di lavoro - 4. I controlimiti alla disapplicazione della direttiva - 5. L’obbligo giudiziario di conformazione del diritto nazionale a quello europeo - 6. Il divieto di discriminazione sul lavoro alla stregua della Carta dei diritti del cittadino europeo.No difference of treatment on grounds of religion or belief and religious organizationsABSTRACT: It’s the first time that the Court of Justice E.U. deals with the limits of the exemption from ban on discrimination on grounds of religion or belief in favour of organisations the ethos of which is based on religion or belief. The German law implemented softly the directive 2000/78/CE favouring that ethos, as interpreted by those organizations, and consequently limiting the judicial review merely to its plausibility. Viceversa according to the European Court the religion or belief must constitute a genuine, legitimate and justified occupational requirement, having regard to the organisation’s ethos and the proportionality principle (even though not explicitly recalled by the directive). So an exhaustive judgement allows an objective, not spiritualistic, evaluation of the occupational activities and therefore a stronger legal protection of workers under articles 10, 21 and 47 of the Charter of Fundamental Rights of the European Union.